Creatine, carbs, and fluids: How important in soccer nutrition? - Kirkendall, D. T. (Sports Science Exchange, 2004)
The focus in this review will be on nutritional items in soccer - creatine, carbohydrate foods, and fluid replacement drinks. Summary: There is no persuasive evidence that creatine supplementation is beneficial to soccer play. Because most of the running in soccer is at less than maximal speed, it is unlikely that creatine supplementation would have any important benefits. On the other hand, soccer is a glycogen-dependent sport, making carbohydrate feedings repletion of critical importance. Therefore, the ability to sustain late-game running speed and goal-scoring and to avoid injuries are dependent on glycogen levels. Adequate dietary carbohydrate in the days and hours before strenuous training and competition is critical to maintaining adequate glycogen levels in the muscles. Similar to the detrimental effect of inadequate carbohydrate intake, even slight dehydration can be detrimental to impair performance in soccer, and sports drinks containing moderate amounts of carbohydrate and electrolytes, especially sodium, are better than plain water in maintaining hydration during soccer play and in rehydrating during recovery. Soccer players typically do not eat enough carbohydrate and begin soccer matches with less than optimal stores of muscle glycogen. Moreover, they usually do not drink enough fluids during practice and competition to adequately replace their sweat losses. Coaches and athletic trainers must continually reinforce the need for dietary carbohydrate and fluid replenishment, ensure that fluids are available on the sidelines, and, when possible, supervise the eating and drinking behavior of the players. All levels of play can benefit by following sound nutritional guidelines.